Actor model software abstraction for concurrency and distribution - Pham, Nguyen Dinh (Quezon City College of Engineering, University of the Philippines Diliman, 2013)
Multicore hardware requires concurrency for maximum utilization. However, in shared memory concurrent systems, using low-level synchronization primitives is challenging. Besides that, with abundant connectivity, software should leverage distribution computation, which is naturally a message passing environment rather that shared memory. The Actor model abstracts those requirements by regarding the system as a set of isolated concurrent entities, communicating via asynchronous messages. In this work, we studied the software implementation of Actor model abstraction. Beside the problem of realizing the model's principles, there are also engineering problems to be considered, where different programming languages and runtime systems provide different levels of support. Focusing on the Java Virtual Machine, with Scala language in particular, we built silf, an actor library aiming at simplicity and scalability. Benchmarking indicates that silf has comparable performance with other well-established implementations.
Thesis (M.S. Computer Science)--University of the Philippines, Diliman.
Keywords: Computer multitasking; Scala (Computer program language).; Actor model (Computer science).; Concurrent programming